ESTABLISHING THE FACTORIAL VALIDITY, RELIABILITY AND USABILITY OF META-COGNITIVE AWARENESS INVENTORY IN PHYSICS (MAIP) FOR MALE AND FEMALE STUDENTS IN NIGERIA - Barnabas Obiaje Ellah (Al-Hijr: Journal of Adulearn World, 2026)
The study was on establishment of factorial validity, reliability and usability of Meta-cognitive Awareness Inventory in Physics (MAIP) for male and female students in Nigeria. Three research questions which guided the study were answered. One null hypothesis was formulated and tested at 0.05 level of significance. The study adopted instrumentation research design. The population for the study comprised all the 15030 Senior Secondary Two (SSII) science students in the 2319 Secondary Schools. The sample comprised 1382 SSII male and female students that offered Physics as a school subject for 2020/2021 Academic Session. The instrument for data collection was Meta-cognitive Awareness Inventory in Physics (MAIP). The Meta-cognitive Awareness Inventory in Physics (MAIP) was face validated by five experts and the observations of these experts were used for the review of the items of the instrument. Construct validation was carried out on the Meta-cognitive Awareness Inventory in Physics (MAIP) for secondary schools to establish its construct validity using factor analysis. This is based on the extraction method of principal component analysis and rotation method of Varimax with Kaiser Normalization. The item selection was done using the rotated component matrix. The items with factor loading of 0.40 and above on any of the factors were identified and selected to form part of the instrument. Coefficient of internal consistency was obtained through Cronbach’s Alpha and found to be 0.78. Research question 1 was answered using factor analysis. Research question 2 was answered using coefficient of internal consistency obtained through Cronbach’s Alpha. Research question 3 was answered using mean and standard deviations. The null hypothesis was tested using independent t-test at 0.05 level of significance. The findings revealed that Meta-cognitive Awareness Inventory in Physics (MAIP) for Senior Secondary students in Benue State has 52 factorially simple or pure items and 23 factorially complex items in terms of their factor loadings. The coefficient of internal consistency of Meta-cognitive Awareness Inventory in Physics (MAIP) for Senior Secondary students in Benue State was found to be 0.98. It was also found that there was statistical significant difference in the mean meta-cognitive awareness ratings of male and female students in favour of female students using Meta-cognitive Awareness Inventory in Physics (MAIP). It was recommended among others that Physics teachers should use the Meta-cognitive Awareness Inventory in Physics (MAIP) to determine their students’ level of meta-cognitive awareness in the schools. This may enable them to gain awareness and control over themselves as learners for effective learning of Physics in secondary schools irrespective of their gender.